2021
DOI: 10.3390/microorganisms9040813
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium myocastoris n. sp. (Apicomplexa: Cryptosporidiidae), the Species Adapted to the Nutria (Myocastor coypus)

Abstract: Cryptosporidium spp., common parasites of vertebrates, remain poorly studied in wildlife. This study describes the novel Cryptosporidium species adapted to nutrias (Myocastor coypus). A total of 150 faecal samples of feral nutria were collected from locations in the Czech Republic and Slovakia and examined for Cryptosporidium spp. oocysts and specific DNA at the SSU, actin, HSP70, and gp60 loci. Molecular analyses revealed the presence of C. parvum (n = 1), C. ubiquitum subtype family XIId (n = 5) and Cryptosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 106 publications
(109 reference statements)
3
26
0
Order By: Relevance
“…As inferring the evolutionary relationships of Cryptosporidium spp. using SSU sequences alone can lead to erroneous conclusions [54,57,58], we included other polymorphic loci for our analyses. Although some previous studies have shown polymorphism in actin, HSP70, and TRAP-C1 genes in Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…As inferring the evolutionary relationships of Cryptosporidium spp. using SSU sequences alone can lead to erroneous conclusions [54,57,58], we included other polymorphic loci for our analyses. Although some previous studies have shown polymorphism in actin, HSP70, and TRAP-C1 genes in Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…(165); Microtus pennsylvanicus (13); A. agrarius (13); Ondatra zibethicus (8); Spermophilus beecheyi (149); Sciurus carolinensis (6); Tamiasciurus hudsonicus (9); Tamias striatus (38); Marmota monax (2); Castor canadensis (2); Castor fiber (16); Erethizon dorsatum (2); Hydrochoerus hydrochaeris (8); Cavia porcellus (1); Chinchilla lanigera (3); Phodopus sungorus (4); Myocastor coypus (1); Rhizomys sinensis (158); Rattus tanezumi (3); Marmota flaviventris (33); Wild rat (13); Qinghai vole (3) IIaA15G2R1; IIaA16G2R1; IIaA17G2R1; IIaA18G1R1b; IIaA18G3R1; IIdA15G1; IIiA10; IIpA9; IIpA6; IIoA15G1; IIoA13G1 [ 5 , 37 , 80 , 87 , 24 , 64 ] C. meleagridis Turkey ( Meleagris gallopavo ) Birds, humans Commonly reported R. norvegicus (1); R. rattus (1); Wild rat (1) [ 38 , 65 , 80 ] C. ubiquitum Cattle ( B. taurus ) Ruminants, rodents, primates Commonly reported R. norvegicus (1); C. lanigera (49); Siberian flyingsquirrel (1); M. coypus (5); Callosciurus erythraeus (19); Wild rat (10); Laboratory rats (1); Qinghai vole (1) XIIa; XIId; XIIi [ 5 , 11 , 40 , 42 , 43 , 46 ] C. viatorum Human ( Homo sapiens ) Rodents Many reported leopoldamys edwardsi (11); swamp rats (3); Wild rats (25) XVbA2G1; XVaA6; XVaA3g; XVaA3h; XVcA2G1; XVcA2G1a; XVcA2G1b; XVdA3 [ 52 , 66 , 91 ] C . muris …”
Section: Molecular Characteristics Of Cryptosporidium In Rodentsmentioning
confidence: 99%
“…The species has a broad host range that includes primates, carnivores, ruminants, and various rodents [ 46 , 94 ]. There are increasing research reports of C. ubiquitum being detected in rodents, and the host range has been expanding to include rodents such as wild squirrels, chipmunks, field mice, brown rats, Myocastor coypus , pet C. lanigera , farm bamboo rats, and laboratory mice [ 40 , 42 , 43 , 46 , 53 , 62 , 67 , 74 , 77 , 81 ]. In the USA, a study showed that transmission of C. ubiquitum to humans from rodents was likely to come from drinking untreated water contaminated by wildlife urine or feces [ 11 ].…”
Section: Public Health Of Zoonotic Cryptosporidium Sppmentioning
confidence: 99%
“…Sequence analyses of housekeeping genes including the small subunit ( ssu rRNA) or the internal transcribed spacer (ITS) region of the ribosomal RNA gene have revealed a high degree of genetic diversity within Cryptosporidium spp., G. duodenalis , Blastocystis sp., and E. bieneusi , leading to the identification of several genotypes/subtypes with marked differences in host specificity and range ( Franzén et al, 2009 ; Stensvold et al, 2012 ; Li and Xiao, 2019 ; Garcia-R et al, 2020 ). Thus, the genus Cryptosporidium encompasses at least 46 valid species, with C. hominis and C. parvum causing most of the infections reported in humans and NHP globally ( Ježková et al, 2021 ; Zahedi et al, 2021 ). Giardia duodenalis is constituted of eight (A to H) distinct genetic assemblages, of which zoonotic assemblages A and B are able to infect a wide diversity of mammal species including humans and NHP ( Ryan and Cacciò, 2013 ).…”
Section: Introductionmentioning
confidence: 99%